2019
DOI: 10.1088/1741-4326/ab3bd5
|View full text |Cite
|
Sign up to set email alerts
|

Reduced model for direct induction startup scenario development on MAST-U and NSTX-U

Abstract: A reduced semi-empirical model using time-dependent axisymmetric vacuum field calculations is used to develop the prefill and feed-forward coil current targets required for reliable direct induction (DI) startup on the new MA-class spherical tokamaks, MAST-U and NSTX-U. The calculations are constrained by operational limits unique to each device, such as the geometry of the conductive elements and active coils, power supply specifications and coil heating and stress limits. The calculations are also constraine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…During the plasma breakdown, the electron density increases from the natural ionisation level to 10 15 -10 17 m −3 with an electron avalanche. Because the magnetic field lines are not closed initially, the electron energy is bounded by the free-streaming limit [6,51,52], E e = EL c /4 ≈ 250 eV for E = 0.5 V m −1 and L c = 2000 m. Only after the magnetic configuration is closed with a substantial plasma current, the electron can run away to relativistic energies. For the JT-60SA parameter, the typical plasma current after an electron avalanche is expected to be about 200 A, which increases to 10-15 kA at the time when hydrogen is fully ionised (burn-through).…”
Section: Runaway Electron Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…During the plasma breakdown, the electron density increases from the natural ionisation level to 10 15 -10 17 m −3 with an electron avalanche. Because the magnetic field lines are not closed initially, the electron energy is bounded by the free-streaming limit [6,51,52], E e = EL c /4 ≈ 250 eV for E = 0.5 V m −1 and L c = 2000 m. Only after the magnetic configuration is closed with a substantial plasma current, the electron can run away to relativistic energies. For the JT-60SA parameter, the typical plasma current after an electron avalanche is expected to be about 200 A, which increases to 10-15 kA at the time when hydrogen is fully ionised (burn-through).…”
Section: Runaway Electron Modellingmentioning
confidence: 99%
“…where E is the electric field in V m −1 and p is the neutral pressure in Pa. The analyses of the breakdown time in NSTX [52] and KSTAR [87] have shown that the Townsend model of equation is insufficient for reproducing the timescale of experimental I p and n e rises, and a mechanism for shielding applied electric fields is required. Numerical studies using PIC simulations [87][88][89][90] have proposed that when ionisation proceeds, self-consistent electric fields formed by the charge separation of electrons and ions shield the applied electric field and retard the breakdown.…”
Section: Appendix a Townsend Avalanche Model In The Index-s Codementioning
confidence: 99%
See 1 more Smart Citation
“…This should be due to the feature in a spherical torus where E φ /p (kV m −1 Torr −1 ) is high. It was reported that free acceleration of electrons in a spherical torus could shorten the time of electron avalanche phase [20]. However, in the case there is a significant delay in the electron avalanche for some reasons e.g.…”
Section: Plasma Volume Modelmentioning
confidence: 99%
“…There are two plasma initiation scenarios in MAST, namely merging compression and direct induction [20,25]. Figure 2 shows the solenoid and poloidal field coils in MAST.…”
Section: Ohmic Plasma Initiation With Direct Induction Scenario In Mastmentioning
confidence: 99%